2021
DOI: 10.1111/anu.13303
|View full text |Cite
|
Sign up to set email alerts
|

Fermented corn protein concentrate to replace fishmeal in practical diets for Pacific white shrimp Litopenaeus vannamei

Abstract: The latest corn-based ingredient available in the market today is fermented corn protein concentrate (FCPC), which is expected to perform well in shrimp diets due to its nutritional profile and the probiotic properties of the product. The current study was conducted to evaluate the efficacy of FCPC as a replacement for fish meal (FM) in diets of Pacific white shrimps, Litopenaeus vannamei. Graded levels of FCPC (0, 4, 8, 11, 13 and 15 g/100 g) were used to replace fishmeal (16, 12, 8, 4, 2 and 0 g/100 g) in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In the present study, significant differences were observed in final biomass, final mean weight and the thermal growth coefficient among the treatments. The differences could be attributed to the addition of 6) could be the reason for similar growth performance among shrimp fed with the experimental diets and the basal diet (Galkanda-Arachchige et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, significant differences were observed in final biomass, final mean weight and the thermal growth coefficient among the treatments. The differences could be attributed to the addition of 6) could be the reason for similar growth performance among shrimp fed with the experimental diets and the basal diet (Galkanda-Arachchige et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Galkanda‐Arachchige et al. (2021) reported the efficacy of FCPC as the latest advance products of corn‐based ingredients to maintain the growth, FCR and survival of shrimp L. vannamei with gradual inclusion from 4% to 15% to partially and completely replace the use of FM in the diet. The authors suggest that the better nutritional profile with no deficiencies in amino acids (Table 6) could be the reason for similar growth performance among shrimp fed with the experimental diets and the basal diet (Galkanda‐Arachchige et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations